Evaluation and Strategy of New-type Urbanization Policy Based On S-CAD Method - A Case Study of Wuhan, China. Issue 3 (May 2020) - Wei, Wei; Li, Mengchen; Jiao, Yongli
Abstract: Using S-CAD policy evaluation method to carry out effect, economic and feasibility analysis on Wuhan's new urbanization policy, the evaluation results show that the logic, needs and feasibility of the policy elements are good, and the adequacy of the policy chain is relatively inadequate, Wuhan's various policies promote new-type urbanization effectively and implement the central-level strategies and goals. The next step is to increase efforts to promote equalization of public services, regional coordinated development, and urban quality improvement. Through the case study of Wuhan, it is verified that the S-CAD method is a meta-method and policy evaluation system that combines political wisdom and scientific knowledge, taking into account qualitative judgment and quantitative analysis, and can be applied to the evaluation of new urbanization construction in cities.